Silicone pressure-sensitive adhesive composition having polysiloxane containing methyl phenyl group, silicone pressure-sensitive adhesive film, method of manufacturing the same
The silicone adhesive composition with a controlled AnB structure in polysiloxane addresses adhesion and flexibility issues in extreme environments, ensuring low glass transition temperatures and high peel strength while preserving optical transparency.
Patent Information
- Application Number
- KR1020250159717
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2025-10-29
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-10-29
AI Technical Summary
Conventional silicone adhesives with a dimethyl polysiloxane structure face challenges in maintaining adhesion, peel strength, and flexibility in extreme environments, particularly in cryogenic conditions, and introducing phenyl groups for flexibility reduces optical transparency due to refractive index differences.
A silicone adhesive composition comprising a polysiloxane with a methylphenyl group, featuring a dimethylsiloxane and methylphenylsiloxane chemically bonded in an AnB structure, controlled for molecular weight and phenyl group arrangement, which enhances flexibility and adhesion while maintaining optical transparency.
The composition achieves low glass transition temperatures, high peel strength, and maintains flexibility and optical clarity by controlling phenyl group distribution, suitable for extreme environments.
Smart Images

Figure 112025120915548-PAT00018_ABST
Abstract
Description
Technology Field
[0001] The technical concept of the present invention relates to a silicone adhesive composition comprising a polysiloxane containing a methylphenyl group, a silicone adhesive film, and a method for manufacturing the same. Background Technology
[0002] Silicone adhesives are used in various industrial fields based on their excellent heat resistance, chemical resistance, and structural stability. In particular, they offer the advantage of providing stable adhesive performance over a wider temperature range compared to acrylic adhesives. This is attributed to the inorganic framework structure and high free volume of silicone polymers. However, to meet the requirements for extreme environments and durability under variable stress demanded by flexible displays, high-flexibility batteries, and wearable devices, simply ensuring low temperature performance is no longer sufficient. Excellent adhesion to the substrate, initial tack, and high-reliability peel strength are emerging as important performance factors.
[0003] Conventional silicone adhesives with a dimethyl polysiloxane structure have excellent heat resistance and chemical stability, but they have limitations such as reduced adhesion, reduced peel strength, and loss of flexibility in cryogenic environments. In addition, adding various siloxane polymers to improve low-temperature performance leads to a problem of reduced adhesion. As an alternative, phenyl groups are introduced to increase free volume to suppress aggregation between silicone chains and provide flexibility, but this requires a large amount, and there is a limitation in that optical transparency is reduced due to the high difference between the refractive index of the phenyl groups and the refractive index of dimethyl siloxane. The problem to be solved
[0004] The technical problem that the technical concept of the present invention aims to solve is to provide a silicone adhesive composition containing a polysiloxane containing a methylphenyl group, a silicone adhesive film, and a method for manufacturing the same.
[0005] However, these tasks are exemplary, and the technical concept of the present invention is not limited thereto. means of solving the problem
[0006] According to one aspect of the present invention, a silicone adhesive composition comprising a polysiloxane containing a methylphenyl group, a silicone adhesive film, and a method for manufacturing the same are provided.
[0007] According to one embodiment of the present invention, the silicone adhesive composition comprises a polysiloxane adhesive having at least one vinyl group; and a polysiloxane containing a methylphenyl group that is cross-linked with the polysiloxane adhesive, wherein the polysiloxane containing the methylphenyl group comprises a dimethyl siloxane (A); and a methylphenyl siloxane (B) chemically bonded to the dimethyl siloxane, and the repeating unit may be AnB (wherein n is 15 or more and 300 or less).
[0008] According to one embodiment of the present invention, the silicone adhesive composition is -20 o It can have a glass transition temperature of C or lower.
[0009] According to one embodiment of the present invention, the silicone adhesive composition may have a peel strength of 1310 gf / in or more.
[0010] According to one embodiment of the present invention, in the silicone adhesive composition, the polysiloxane adhesive and the polysiloxane containing methylphenyl groups may be contained in a weight ratio of 2:1 to 10:1.
[0011] According to one embodiment of the present invention, the polysiloxane containing the methylphenyl group may have a molecular weight of 10,000 g / mol to 1,000,000 g / mol.
[0012] According to one embodiment of the present invention, the polysiloxane containing a methylphenyl group may have the following chemical formula.
[0013]
[0014] (Here, n is between 15 and 300 inclusive, and m is between 2 and 256 inclusive)
[0015] According to one embodiment of the present invention, the dimethylsiloxane may be composed of a siloxane oligomer having the following chemical formula.
[0016]
[0017] According to one embodiment of the present invention, the methylphenylsiloxane may have the following chemical formula.
[0018]
[0019] According to one embodiment of the present invention, in the polysiloxane containing the methylphenyl group, the portion where the dimethyl siloxane and the methylphenyl siloxane are bonded may have the following chemical formula.
[0020]
[0021] According to one embodiment of the present invention, the polysiloxane containing the methylphenyl group may have at least one end portion containing a vinyl group of the following chemical formula.
[0022]
[0023] According to one embodiment of the present invention, the methylphenylsiloxane may be in the range of 0.1 mol% to 5 mol% with respect to the number n of repeating units of the dimethylsiloxane in the polysiloxane containing the methylphenyl phenyl group.
[0024] According to one embodiment of the present invention, the polysiloxane containing the methylphenyl group may have a structure in which the An is disposed at each of both ends.
[0025] According to one embodiment of the present invention, the polysiloxane adhesive may comprise at least one of dimethyl polysiloxane, dimethyl diphenyl polysiloxane, dimethyl-methylphenyl polysiloxane, polydimethylsiloxane (PDMS), polymethylphenylsiloxane, dimethylsiloxane-methylphenylsiloxane copolymer, and dimethylsiloxane-diphenylsiloxane copolymer.
[0026] According to one embodiment of the present invention, the polysiloxane adhesive may further include a resin composed of a network-type oligomer and having a vinyl group or a hydride group at the end.
[0027] According to one embodiment of the present invention, the silicone adhesive composition may further include a crosslinking agent comprising at least one of dicumyl peroxide (DCP), 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane (DBPH), benzoyl peroxide (BPO), 2,4-dichlorobenzoyl peroxide (DBP), t-butyl peroxybenzoate (TBB), and α,α'-bis(t-butylperoxy)diisopropylbenzene (BIPB).
[0028] According to one embodiment of the present invention, the silicone adhesive film comprises a film substrate; and a silicone adhesive composition applied and cured on the film substrate, wherein the silicone adhesive composition comprises a polysiloxane adhesive having at least one vinyl group at a terminal end; and a polysiloxane containing a methylphenyl group cross-linked to the polysiloxane adhesive, wherein the polysiloxane containing a methylphenyl group comprises dimethylsiloxane (A); and a methylphenylsiloxane (B) chemically bonded to the dimethylsiloxane, and the repeating unit may be AnB (wherein n is 15 or more and 300 or less).
[0029] According to one embodiment of the present invention, the silicone adhesive composition is -20 o It can have a glass transition temperature of C or lower and a peel strength of 1310 gf / in or higher.
[0030] According to one embodiment of the present invention, a method for manufacturing the silicone adhesive film comprises the steps of: kneading a polysiloxane adhesive having at least one vinyl group and a polysiloxane containing a methylphenyl group to form a mixture; adding a crosslinking agent and a platinum catalyst to the mixture and kneading to form a silicone adhesive composition; applying the silicone adhesive composition onto a film substrate; and curing the silicone adhesive composition, wherein the polysiloxane containing a methylphenyl group comprises dimethylsiloxane (A); and methylphenylsiloxane (B) chemically bonded to the dimethylsiloxane, and the repeating unit may be AnB (wherein n is 15 or more and 300 or less).
[0031] According to one embodiment of the present invention, a polysiloxane containing a methylphenyl group can be manufactured by a manufacturing method comprising the steps of: stirring a siloxane oligomer and a retardant to form a first mixture; stirring the first mixture and methylphenyl siloxane to form a second mixture; stirring the second mixture and a platinum catalyst to form a third mixture; and heating the third mixture to polymerize the siloxane oligomer and the methylphenyl siloxane.
[0032] According to one embodiment of the present invention, after performing the polymerization step, methylphenylsiloxane can be added to the polysiloxane formed by polymerization to form a polysiloxane having a desired molecular weight, and the polymerization reaction can be repeated. Effects of the invention
[0033] According to the technical concept of the present invention, a polysiloxane containing methylphenyl groups can control physical properties by controlling the degree of crystallinity while reducing the content of expensive phenyl groups, thereby enabling simultaneous achievement of cost reduction and improved functionality. The polysiloxane containing methylphenyl groups can be utilized as a high-performance material capable of maintaining stable physical properties even in extreme environments, while increasing the freedom of material design compared to existing materials through precise control of the arrangement of phenyl groups.
[0034] Accordingly, the silicone adhesive composition containing a polysiloxane containing a methylphenyl group according to the present invention can effectively lower the glass transition temperature while maintaining excellent adhesive strength even in low-temperature environments by introducing an AnBAnB type linear polymer structure in which phenyl groups are periodically arranged.
[0035] According to the present invention, by providing a linear polysiloxane in which phenyl groups are introduced to improve low-temperature performance but methylphenyl groups are regularly arranged in an AnB structure, the free volume of the silicone adhesive is increased and chain fluidity is improved to maintain flexibility even in a low-temperature environment, and optical performance can be maintained as is because the increase in the refractive index of the raw material is not significant. Since the linear polysiloxane is designed with a molecular weight in the range of 10,000 to 300,000 g / mol, it is easy to disperse within the adhesive without an excessive increase in viscosity, and low-temperature performance can be enhanced without impairing tack and peel strength.
[0036] The silicone adhesive composition comprising a polysiloxane containing a methylphenyl group according to the present invention can be applied to flexible displays, high-flexibility batteries, wearable devices, etc., and can be used particularly in extreme environments.
[0037] The effects of the present invention described above are illustrative and the scope of the present invention is not limited by these effects. Brief explanation of the drawing
[0038] FIG. 1 illustrates a method for manufacturing a polysiloxane containing a methylphenyl group included in a silicone adhesive composition according to one embodiment of the present invention using a chemical formula. FIG. 2 is a flowchart illustrating a method for manufacturing a polysiloxane containing a methylphenyl group included in a silicone adhesive composition according to an embodiment of the present invention. FIG. 3 is a flowchart illustrating a method for manufacturing a silicone adhesive film comprising a polysiloxane containing a methylphenyl group according to an embodiment of the present invention. Specific details for implementing the invention
[0039] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the attached drawings. The embodiments of the present invention are provided to more completely explain the technical concept of the present invention to those skilled in the art, and the following embodiments may be modified in various different forms, and the scope of the technical concept of the present invention is not limited to the following embodiments. Rather, these embodiments are provided to make the present disclosure more faithful and complete and to fully convey the technical concept of the present invention to those skilled in the art. In this specification, the same reference numerals denote the same elements throughout. Furthermore, various elements and areas in the drawings are depicted schematically. Accordingly, the technical concept of the present invention is not limited by the relative sizes or spacing depicted in the attached drawings.
[0040] The technical concept of the present invention is to provide a silicone adhesive composition comprising a polysiloxane containing a methylphenyl group having excellent adhesive strength that can be applied to flexible displays, high-flexibility batteries, wearable devices, etc.
[0041] In the following, polysiloxanes containing methylphenyl groups will be described in detail.
[0042] Polysiloxane containing methylphenyl groups
[0043] Polysiloxanes containing methylphenyl groups can effectively suppress chain crystallization at low temperatures with only a minimal introduction of phenyl groups by precisely controlling the position and periodicity of the phenyl groups present within the polysiloxane chain.
[0044] The above-mentioned polysiloxane containing a methylphenyl group comprises dimethyl siloxane (A); and methylphenyl siloxane (B) chemically bonded to the dimethyl siloxane, and the repeating unit may be AnB (wherein n is 15 or more and 300 or less).
[0045] The above repetition unit may be repeated m times (where m is between 2 and 256).
[0046] The polysiloxane containing the methylphenyl group may have a structure in which the An is disposed at each of the two ends.
[0047] The polysiloxane containing the methylphenyl group may have a molecular weight of 10,000 g / mol to 1,000,000 g / mol. If the molecular weight is less than 10,000 g / mol, the flowability is low, making it difficult to commercialize. If the molecular weight exceeds 1,000,000 g / mol, there are difficulties in the formulation and processing of polymer materials. For example, if the molecular weight is 100,000 g / mol, it can provide the advantages of excellent flowability and processability in commercialization of products such as sealants, adhesives, and rubber.
[0048] The above-mentioned polysiloxane containing a methylphenyl group may have the following chemical formula. Here, n is 15 or more and 300 or less, and m is 2 or more and 256 or less.
[0049]
[0050] The above dimethylsiloxane may be composed of a siloxane oligomer having the following chemical formula.
[0051]
[0052] The above methylphenylsiloxane may have the following chemical formula.
[0053]
[0054] In the polysiloxane containing the methylphenyl group, the portion where the dimethyl siloxane and the methylphenyl siloxane are bonded may have the following chemical formula. Here, the central carbon atoms may be bonded by a single bond.
[0055]
[0056] The polysiloxane containing the methylphenyl group may have a terminal portion containing a vinyl group of the following chemical formula at at least one end. For example, the polysiloxane containing the methylphenyl group may have the vinyl group at both ends.
[0057]
[0058] In the polysiloxane containing the methylphenyl group, the periodicity of the phenyl group of the methylphenyl siloxane can be determined by the molecular weight of the siloxane oligomer. That is, if the siloxane oligomer is long, the phenyl group can be arranged to have long periodicity.
[0059] The molecular weight can be increased through step polymerization. For example, when An, B, and An are polymerized, it may have the structure AnBAn; when AnBAn, B, and AnBAn are polymerized, it may have the structure AnBAnBAnBAn; and when AnBAnBAnBAn, B, and AnBAnBAnBAn are polymerized, it may have the structure AnBAnBAnBAnBAnBAnBAnBAnBAnBAn. Here, it should be noted that An does not represent a single functional group of (CH3)2-Si-O, but refers to n dimethylsiloxane structures represented as [(CH3)2-Si-O]n, which may be an oligomer.
[0060] For example, when considering an ABAB alternating structure, if A is a single functional group of (CH3)2-Si-O, the cluster size of A differs from that of the present invention. In such an ABAB alternating structure, the flexibility characteristic of siloxane is lost, leading to brittleness, an increase in the glass transition temperature (Tg), and an increase in the refractive index, resulting in increased opacity, among other limitations.
[0061] The above polysiloxane containing methylphenyl groups has an alternating AnBAnB structure, wherein An comprises dimethylsiloxane having n clusters rather than a single functional group. Accordingly, the flexibility of the siloxane chain can be maintained, and the methylphenylsiloxane (B), which is periodically and sparsely arranged, can act as an inter-chain aggregation at high temperatures.
[0062] Here, n may be 15 or more and 300 or less, and preferably n may be 30 or more and 300 or less. If n is less than 15, brittleness may occur and the glass transition temperature (Tg) may increase. If n is greater than 300, the periodicity of the methylphenylsiloxane (B) being placed becomes too long, and the effect of the methylphenylsiloxane (B) becomes negligible.
[0063] The methylphenylsiloxane (B) may be in the range of 1 mol% to 5 mol% with respect to the number of repeating units n of "-Si-(CH3)2-O-" in the polysiloxane containing the methylphenyl group, i.e., in the dimethylsiloxane (A).
[0064] The above-mentioned polysiloxane containing a methylphenyl group is, for example, -80 o It can have a glass transition temperature of less than C. The polysiloxane containing the methylphenyl group is, for example, -130 o C or higher -80 o It can have a glass transition temperature of less than C.
[0065] The above glass transition temperature is -80 o If the temperature exceeds C, brittleness may occur, leading to a decrease in airtightness performance. For example, in the case of O-rings used to prevent hydrogen leakage in cryogenic hydrogen storage containers, the operating temperature is -70°C o About 10 times C o It must have a glass transition temperature or crystallization temperature with a safety margin of C or lower, thereby ensuring stability when used in cryogenic environments.
[0066] When the above-mentioned polysiloxane containing a methylphenyl group has a molecular weight of about 100,000 g / mol, for example, 25 o It may have a first viscosity in the range of 63,000 cP to 70,000 cP at a temperature of C. In addition, the polysiloxane containing the methylphenyl group is, for example, 80 o It can have a second viscosity in the range of 13,000 cP to 15,000 cP at a temperature of C.
[0067] 25 o 80 relative to the first viscosity at a temperature of C o The viscosity reduction rate of the second viscosity at a temperature of C may, for example, be less than 0.8, may be in the range of 0.6 or more and less than 0.8, or may be in the range of 0.7 or more and less than 0.8. The viscosity reduction rate must satisfy less than 0.8 in order to maintain performance at room temperature at high temperature. If the viscosity reduction rate is 0.8 or more, durability problems such as a decrease in adhesive strength or an increase in permanent extrusion reduction rate may occur when manufacturing high-temperature application devices such as sealants, adhesives, rubber, etc.
[0068] The above-mentioned polysiloxane containing a methylphenyl group can be manufactured by the manufacturing method described below. However, this is exemplary, and various manufacturing methods are included within the technical scope of the present invention.
[0069] Method for manufacturing a polysiloxane containing a methylphenyl group
[0070] FIG. 1 illustrates a method for manufacturing a polysiloxane containing a methylphenyl group included in a silicone adhesive composition according to one embodiment of the present invention using a chemical formula.
[0071] Referring to FIG. 1, the polysiloxane containing the methylphenyl group may use a siloxane oligomer containing dimethyl siloxane (A) having vinyl groups as both end groups and a methylphenyl siloxane (B) having hydride groups as both end groups that can react with the oligomer to form a linear chain.
[0072] The above-mentioned polysiloxane containing a methylphenyl group can be formed by the reaction of the vinyl group (CH2=CH-) of the siloxane oligomer and the hydride group (H-) of the methylphenyl siloxane. That is, it can be formed by a hydrosilylation reaction. Accordingly, the above-mentioned polysiloxane containing a methylphenyl group comprises dimethyl siloxane (A); and methylphenyl siloxane (B) chemically bonded to the dimethyl siloxane, and the repeating unit may be AnB (where n is 15 or more and 300 or less). The above-mentioned repeating unit may be repeated m times (where m is 2 or more and 256 or less). Accordingly, the above-mentioned polysiloxane containing a methylphenyl group may have a molecular weight of 10,000 g / mol to 1,000,000 g / mol.
[0073] This reaction can be carried out based on a platinum (Pt) catalyst. Here, reactions between vinyl groups or between hydride groups do not occur, and thus it is an excellent reaction for repeatable structure control.
[0074] In the above-mentioned polysiloxane containing methylphenyl groups, control of the phenyl group structure within the polysiloxane for improving low-temperature performance can be achieved through step polymerization of a dimethyl siloxane oligomer and a methylphenyl siloxane monomer.
[0075] FIG. 2 is a flowchart illustrating a method for manufacturing a polysiloxane containing a methylphenyl group included in a silicone adhesive composition according to an embodiment of the present invention.
[0076] Referring to FIG. 2, a method (S100) for manufacturing a polysiloxane containing a methylphenyl group comprises the steps of: stirring a siloxane oligomer and a retardant to form a first mixture (S110); stirring the first mixture and methylphenyl siloxane to form a second mixture (S120); stirring the second mixture and a platinum catalyst to form a third mixture (S130); and heating the third mixture to polymerize the siloxane oligomer and the methylphenyl siloxane (S140).
[0077] Before performing the step (S110) of forming the first mixture, a step of nitrogen purging of the reaction vessel containing the siloxane oligomer and the retardant may be further performed. Impurities and moisture present in the reaction vessel can be removed by such nitrogen purging.
[0078] The step (S110) of forming the first mixture above can be performed by introducing a siloxane oligomer and a retardant into the reaction vessel and stirring to form the first mixture in which the siloxane oligomer and the retardant are mixed.
[0079] In the step (S110) of forming the first mixture, the stirring may be performed, for example, for 1 minute to 20 minutes, and for example, for about 10 minutes. The stirring is performed at room temperature, for example, 0 o C to 40 o It can be performed at a temperature in the C range.
[0080] The above retardant may be added in a range of 0.01 g to 0.5 g based on 100 g of the above siloxane oligomer, for example. The above retardant may be added in an amount of 0.1 g (i.e., 0.1 phr) based on 100 g of the above siloxane oligomer, for example.
[0081] The above retardant may include, for example, at least one of a phenolic compound, a nitroxy radical compound, an aromatic amine compound, and a sulfur compound. The above retardant may include, for example, at least one of 1-ethylcyclohexanol, hydroquinone (HQ), tert-butylhydroquinone (TBHQ), para-methoxyphenol, 1,2-dihydroxybenzene, 2,2,6,6-tetramethylpiperidine-1-oxyl, phenylene diamine, N,N'-diphenyl-p-phenylenediamine (DPPD), thiourea, and alkyl thiophenol.
[0082] The step (S120) of forming the second mixture may be performed by introducing methylphenylsiloxane into the reaction vessel and stirring the first mixture and the methylphenylsiloxane to form the second mixture in which the siloxane oligomer, the retardant, and the methylphenylsiloxane are mixed.
[0083] In the step (S120) of forming the second mixture, the stirring may be performed, for example, for 1 minute to 20 minutes, and for example, for about 10 minutes. The stirring is performed at room temperature, for example, 0 o C to 40 o It can be performed at a temperature in the C range.
[0084] The step (S130) of forming the third mixture may be performed by introducing a platinum catalyst into the reaction vessel and stirring the second mixture and the platinum catalyst to form the third mixture in which the siloxane oligomer, the retardant, the methylphenylsiloxane, and the platinum catalyst are mixed.
[0085] In the step (S130) of forming the third mixture, the stirring may be performed, for example, for 1 minute to 20 minutes, and for example, for about 10 minutes. The stirring is performed at room temperature, for example, 0 o C to 40 o It can be performed at a temperature in the C range.
[0086] The platinum catalyst can promote the hydrosilylation reaction. The platinum catalyst may be a material formed based on platinum. The platinum catalyst may include, for example, at least one of a Speier catalyst composed of a platinum-chloroplatinic acid-alcohol solution, a Karstedt catalyst composed of a platinum-divinyltetramethyldisiloxane complex, and an Ashby catalyst composed of a platinum-allyl complex.
[0087] The platinum catalyst may be added in an amount ranging from, for example, 0.01 g to 0.1 g based on 100 g of the siloxane oligomer. The platinum catalyst may be added in an amount of, for example, 0.05 g (i.e., 0.05 phr) based on 100 g of the siloxane oligomer.
[0088] The polymerization step (S140) above is, for example, 60 o C to 120 o It can be performed at a temperature in the C range. For example, the polymerization step (S150) may be performed using a reaction vessel containing the second mixture, for example, 60 o C to 120 oIt can be formed by heating the second mixture by placing it in an oil bath maintained at a temperature in the range of C and maintaining it for 1 minute to 10 hours, thereby polymerizing the siloxane oligomer and the methylphenylsiloxane.
[0089] By the above polymerization step (S140), a polysiloxane containing a methylphenyl group can be formed.
[0090] The amount of methylphenylsiloxane added can be controlled according to the molecular weight of the siloxane oligomer.
[0091] For example, the amount (g) of the above-mentioned methylphenylsiloxane can be calculated according to the following formula.
[0092] Amount of methylphenylsiloxane added = (Weight of siloxane oligomer / Molecular weight of siloxane oligomer) x (1 / 2) x (Molecular weight of methylphenylsiloxane)
[0093] The molecular weight of the above methylphenylsiloxane is 270.55 g / mol.
[0094] When the molecular weight of the above siloxane oligomer is 2306 g / mol, the value of n is 29 moles, and the methylphenylsiloxane is 1 mole. In this case, the amount of methylphenylsiloxane added per 100 g of the above siloxane oligomer is 5.87 g. The content of the above methylphenylsiloxane is approximately 1.7 mol% when calculated as 1 / (29 x 2 + 1) x 100.
[0095] When the molecular weight of the above siloxane oligomer is 6832 g / mol, the value of n is 90 moles, and the methylphenylsiloxane is 1 mole. In this case, the amount of methylphenylsiloxane added per 100 g of the above siloxane oligomer is 1.98 g. The methylphenylsiloxane is 1 mole. The content of the methylphenylsiloxane is approximately 0.55 mol% when calculated as 1 / (90x2+1)x 100.
[0096] When the molecular weight of the above siloxane oligomer is 24061 g / mol, the value of n is 322 moles, and the methylphenylsiloxane is 1 mole. In this case, the amount of methylphenylsiloxane added per 100 g of the above siloxane oligomer is 0.56 g. The methylphenylsiloxane is 1 mole. The content of the methylphenylsiloxane is approximately 0.16 mol% when calculated as 1 / (322 x 2 + 1) x 100.
[0097] After performing the polymerization step (S140) above, the polymerization reaction can be repeated by adding methylphenylsiloxane to the polymerized polysiloxane formed to form a polysiloxane having a desired molecular weight. If necessary, a retardant and a platinum catalyst may be further added. This may be referred to as step polymerization.
[0098] The above-mentioned polysiloxane containing methylphenyl groups can be formed by step polymerization. Accordingly, the total molecular weight of the polysiloxane containing methylphenyl groups can be determined according to the number of step polymerizations.
[0099] A first polysiloxane can be formed by first polymerizing the above siloxane oligomer and the above methylphenylsiloxane, and a second polysiloxane can be formed by second polymerizing the first polysiloxane and the added methylphenylsiloxane to form a second polysiloxane in which the first polysiloxane is chemically bonded by the added methylphenylsiloxane. In this way, a third polysiloxane can be formed by tertiarily polymerizing the second polysiloxane and the added methylphenylsiloxane, and an n-th polysiloxane can be formed by repeating the process to perform n-th polymerization.
[0100] For example, we will describe a case where the methylphenylsiloxane is 2 mol% and the number average molecular weight (Mn) of the polysiloxane containing the methylphenyl group is about 100,000 g / mol. As a first step, when the siloxane oligomer having a molecular weight of 2306 g / mol and a structure of An is reacted with the methylphenylsiloxane, a first material having a structure of AnBAn having two terminals of a vinyl group is formed, and the number average molecular weight may be about 4883 g / mol. As a second step, when the first material is reacted again with the methylphenylsiloxane, a second material having a structure of AnBAnBAnBAn is formed, and the number average molecular weight may be about 10,036 g / mol. If this is repeated, the number average molecular weight of the substance formed in the third step may be about 20,342 g / mol, the number average molecular weight of the substance formed in the fourth step may be about 40,954 g / mol, and the number average molecular weight of the substance formed in the fifth step may be 82,179 g / mol.
[0101] The above number average molecular weight is based on theoretical calculations, and a material with a deviation of approximately 10% to 20% may be produced depending on experimental conditions.
[0102] Below, experimental examples of polysiloxanes containing methylphenyl groups will be described.
[0103] Experimental example for polysiloxane containing methylphenyl groups
[0104] Preferred experimental examples are presented below to aid in understanding the present invention. However, the following experimental examples are intended only to aid in understanding the present invention and do not limit the present invention. Details not described herein can be sufficiently technically inferred by those skilled in the art, so their description is omitted.
[0105] Experimental examples were manufactured in the following manner.
[0106] A flask was used as a reaction vessel, and moisture and impurities present inside the flask were removed by purging with nitrogen. 100 g of siloxane oligomer and 0.5 phr (0.5 g) of 1-ethylcyclohexanol as a retardant relative to the siloxane oligomer were added to the flask. Subsequently, at room temperature (25 o A first mixture was formed by stirring at 150 rpm with a mechanical stirrer equipped with a Teflon impeller for 10 minutes in C).
[0107] Next, 5.87 g of methylphenylsiloxane was added to the first mixture. Then, at room temperature (25 o A second mixture was formed by stirring at 150 rpm with a mechanical stirrer equipped with a Teflon impeller for 10 minutes in C).
[0108] Next, a platinum catalyst (HA-04C, SI Feliz Co.) was added to the second mixture at a concentration of 0.05 phr (0.05 g) relative to the siloxane oligomer. Subsequently, the mixture was brought to room temperature (25 o A third mixture was formed by stirring in C) for 10 minutes.
[0109] Subsequently, the above third mixture 80 o Polysiloxane was formed by charging it into an oil bath of C and maintaining it for 2 hours to induce a polymerization reaction.
[0110] Subsequently, the step of mixing the manufactured polysiloxane, a retardant, diphenylsiloxane, and a platinum catalyst, followed by a polymerization reaction, was repeated to form experimental examples according to the diphenyl content. Among the following experimental examples, Experimental Example 1 and Experimental Example 2 are included within the scope of the present invention.
[0111] Experimental Example 1 had a molecular weight of 2306 g / mol of the initially added siloxane oligomer, and the content of methylphenylsiloxane in the polysiloxane prepared accordingly was 1.7 mol%.
[0112] Experimental Example 2 had a molecular weight of siloxane oligomer of 6832 g / mol, and accordingly, the content of methylphenylsiloxane in the polysiloxane was 0.55 mol%.
[0113] Experimental Example 3 was performed in the same manner as Experimental Example 1, except that methylphenylsiloxane was not added and only siloxane oligomer was added, to form polysiloxane.
[0114] Experimental Examples 4 and 5 used commercially available materials from GEOKO. The methylphenylsiloxane content in Experimental Example 4 was 5 mol%, and the methylphenylsiloxane content in Experimental Example 5 was 10 mol%. Experimental Examples 4 and 5 are formed using a ring opening method.
[0115] Experimental Example 6 was performed in the same manner as the example to form polysilicon, except that the molecular weight of the siloxane oligomer was 24061 g / mol, and accordingly, the content of methylphenylsiloxane in the polysiloxane was 0.2 mol%.
[0116] The repeating unit of the polysiloxane prepared is AnB for Experimental Example 1, Experimental Example 2, and Experimental Example 6, A for Experimental Example 3, and AABB for Experimental Examples 4 and 5. Here, A is dimethyl siloxane and B is methyl phenyl siloxane.
[0117] The molecular weights of the examples and comparative examples were all at the level of approximately 100,000 g / mol. This was selected because using polysiloxane with a molecular weight of 100,000 g / mol offers excellent flowability and processability in products such as sealants, adhesives, and rubber.
[0118] The examples and comparative examples all included vinyl groups at both ends.
[0119] The glass transition temperature of the above polysiloxane was measured using a TA DSC 250. The measurement method is as follows: 50 o-85 in C o After primary cooling to C, wait 10 minutes, and -85 o 50 in C o After heating to C for the first time, wait 10 minutes, and 50 o -85 in C o After secondary cooling to C, wait 10 minutes, and -85 o 50 in C o During the process of waiting 10 minutes after heating a second time to C, 5 o It was performed by scanning at a speed of C / min.
[0120] The viscosity of the above polysiloxane is 25 o It was measured in C.
[0121] The viscosity of the above polysiloxane was measured using a cone-plate type rotational viscometer (Visco QC300H, Anton Paar). After setting the sampler temperature, 0.5 ml of the sample was aliquoted and sampled, and then the rotational speed (rpm) was set so that the torque value reached 70~80%, and the viscosity value was measured and acquired.
[0122] Table 1 shows the characteristics of polysiloxanes containing methylphenyl groups.
[0123] division Repetitive unit Methylphenylsiloxane content (mol%) glass transition temperature 25 o C viscosity (cP) Experimental Example 1 AnB 2 -80 o Less than C 69,890 Experimental Example 2 AnB 1 -80 o Less than C 67,140 Experimental Example 3 A 0 -42 o C 65,000 Experimental Example 4 AABB 5 -42 o C 73,490 Experimental Example 5 AABB 10 -80 o Less than C 79,640 Experimental Example 6 AnB 0.16 -45 o C 66,500
[0124] Referring to Table 1, the examples are -80 o Satisfies a glass transition temperature of less than C, and 25 o It satisfies a viscosity in the range of 63,000 cP to 70,000 cP at a temperature of C.
[0125] Experimental Example 3 has a glass transition temperature of -80 o It is higher than C and does not satisfy the glass transition temperature range of the present invention.
[0126] Experimental Example 4 has a glass transition temperature of -80 o It is higher than C and does not satisfy the glass transition temperature range of the present invention. In addition, Experimental Example 4 is 25 oThe viscosity at temperature C does not satisfy the scope of the present invention.
[0127] For reference, even if methylphenylsiloxane is introduced to improve the low-temperature properties of Experimental Example 3, if the room temperature viscosity increases by more than 10% compared to Experimental Example 3, it may cause solubility problems and processability problems, which may result in limitations on the amount added during the formulation process for manufacturing parts.
[0128] Experimental Example 5 is -80 o It satisfies the glass transition temperature of the present invention of less than C. However, there is a limitation in that it must contain 10% by weight of expensive methylphenylsiloxane for this purpose. In addition, Experimental Example 5 is 25 o The viscosity at temperature C does not satisfy the scope of the present invention.
[0129] Experimental Example 6 has a glass transition temperature of -80 o It is higher than C and does not satisfy the glass transition temperature range of the present invention. However, Experimental Example 6 is 25 o It satisfies a viscosity in the range of 63,000 cP to 70,000 cP at a temperature of C. Therefore, the methylphenyl content needs to exceed 0.2 weight.
[0130] Silicone adhesive composition
[0131] A silicone adhesive composition according to one embodiment of the present invention comprises: a polysiloxane adhesive having at least one vinyl group; and a polysiloxane containing a methylphenyl group that is cross-linked to the polysiloxane adhesive.
[0132] The above-described polysiloxane containing a methylphenyl group comprises, as described above, a dimethyl siloxane (A); and a methylphenyl siloxane (B) chemically bonded to the dimethyl siloxane, and the repeating unit may be AnB (wherein n is 15 or more and 300 or less). As the above-described polysiloxane containing a methylphenyl group has been described above, a detailed description will be omitted.
[0133] The above polysiloxane adhesive may include at least one vinyl group (-CH=CH2) at both ends or at least one end to enable peroxide crosslinking. Peroxide crosslinking means that a peroxide (RO-OR) is decomposed into radicals (R or OR) by heating, said radicals break the CH bonds of the polymer chains of said vinyl groups to form activated polymer radicals, and then radicals of different polymer chains are combined to form crosslinking.
[0134] The vinyl groups of the polysiloxane adhesive can be cross-linked to each other, and the vinyl groups of the polysiloxane containing the methylphenyl group can also be cross-linked to the vinyl groups of the polysiloxane adhesive.
[0135] The above polysiloxane adhesive may include a polysiloxane material as a silicone gum material. The polysiloxane material included in the above polysiloxane adhesive may be a linear polymer and may include vinyl groups at both ends or at least one end. The above polysiloxane material may have a molecular weight of, for example, 100,000 g / mol to 800,000 g / mol. The above polysiloxane material may be a mixture of materials having various molecular weights, rather than a mixture of materials with a single molecular weight.
[0136] The above polysiloxane adhesive may include, for example, at least one of dimethyl polysiloxane, dimethyl diphenyl polysiloxane, dimethyl-methylphenyl polysiloxane, polydimethylsiloxane (PDMS), polymethylphenylsiloxane, dimethylsiloxane-methylphenylsiloxane copolymer, and dimethylsiloxane-diphenylsiloxane copolymer.
[0137] The above polysiloxane adhesive may further include a resin composed of a network-type oligomer and having vinyl groups or hydride groups at the ends. The resin may have a ladder structure or a random structure.
[0138] In the above polysiloxane adhesive, the polysiloxane material and the resin may be in a weight ratio of 10:1 to 1:10.
[0139] In addition, the silicone adhesive composition may further include a crosslinking agent, for example, a peroxide-based crosslinking agent. The crosslinking agent may crosslink the polysiloxane adhesive and the polysiloxane containing methylphenyl groups. In addition, the crosslinking agent may crosslink the polysiloxane material contained in the polysiloxane adhesive and the resin. The crosslinking agent may have hydride ends and may crosslink by reacting with vinyl groups through these ends.
[0140] The above crosslinking agent may include a peroxide-based crosslinking agent, and may include at least one of, for example, dicumyl peroxide (DCP), 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane (DBPH), benzoyl peroxide (BPO), 2,4-dichlorobenzoyl peroxide (DBP), t-butyl peroxybenzoate (TBB), and α,α'-bis(t-butylperoxy)diisopropylbenzene (BIPB).
[0141] The above crosslinking agent may include, for example, a p-methylbenzoyl peroxide-based crosslinking agent, and may include, for example, C-23N. The above C-23N is an organic peroxide-based crosslinking agent for silicone rubber from Shin-Etsu. The main component contains about 50 weight% of p-methylbenzoyl peroxide. Silicone rubber curing is performed using an atmospheric pressure heat vulcanization method, crosslinking points are formed by radical generation due to heat, and water resistance and mechanical durability can be improved.
[0142] A platinum catalyst may be used when forming the above silicone adhesive composition. Accordingly, the silicone adhesive composition may or may not contain a platinum catalyst. The platinum catalyst can be activated by heat to promote the cross-linking reaction between the hydride and the vinyl group. The platinum catalyst may include materials as described above.
[0143] Based on 100g of the above silicone adhesive composition, the polysiloxane adhesive is in the range of 20g to 40g, the polysiloxane containing methylphenyl groups is in the range of 5g to 20g, the crosslinking agent is included in the range of 0.5g to 2g, and the remainder may be a solvent.
[0144] In the above silicone adhesive composition, the polysiloxane adhesive and the polysiloxane containing methylphenyl groups may be contained in, for example, a weight ratio of 2:1 to 10:1, and for example, a weight ratio of 3:1 to 7:1.
[0145] The above solvent may be at least one of, for example, xylene, toluene, benzene, ethylbenzene, isopropylbenzene, 1,3,5-trimethylbenzene, hexane, heptane, isoparaffin, and cyclohexane.
[0146] In order to maintain adhesive strength at low temperatures, it is desirable that the above silicone adhesive composition has a low glass transition temperature and high peel strength.
[0147] The above silicone adhesive composition has a glass transition temperature of, for example, -20 o It can be less than or equal to C, for example -20 o C to -50 o It could be in the C range.
[0148] The above glass transition temperature is at least -20 o The temperature must be C or lower to enable indoor use or outdoor use in non-extreme environments. At temperatures below the glass transition temperature, cracks may occur in the silicone adhesive composition when exposed to external forces.
[0149] The above silicone adhesive composition may have a peel strength of, for example, 1000 gf / in or more, for example, 1310 gf / in or more, for example, in the range of 1310 gf / in to 1500 gf / in.
[0150] The above peel strength must be at least 1000 gf / in or higher to be usable as an adhesive for displays, electrical and electronic devices, etc. For example, if it is very low, such as 500 gf / in or lower, it cannot maintain the bonding shape of a large display module.
[0151] The above silicone adhesive composition can be used to form a silicone adhesive film.
[0152] silicone adhesive film
[0153] A silicone adhesive film according to the technical concept of the present invention may comprise a film substrate; and a silicone adhesive composition applied and cured on the film substrate.
[0154] The above silicone adhesive composition may include a polysiloxane adhesive having at least one vinyl group at a terminal end; and a polysiloxane containing a methylphenyl group cross-linked to the polysiloxane adhesive.
[0155] The above-mentioned polysiloxane containing a methylphenyl group comprises dimethyl siloxane (A); and methylphenyl siloxane (B) chemically bonded to the dimethyl siloxane, and the repeating unit may be AnB (wherein n is 15 or more and 300 or less).
[0156] The above film substrate may include various materials, for example, polymer materials. The above film substrate may include, for example, a fluorinated release film, and the fluorinated release film may include a fluorinated polymer such as PTFE, PVDF, FEP, etc., or may be a film designed to allow adhesives, silicones, resins, etc. to be easily peeled off by applying a fluorinated coating agent such as fluorosilane or PVDF (Polyvinylidene fluoride) to its surface. However, this is exemplary and the technical concept of the present invention is not limited thereto.
[0157] A silicone adhesive film may be manufactured by the following manufacturing method. However, this is exemplary, and various manufacturing methods are included within the technical scope of the present invention.
[0158] Method for manufacturing a silicone adhesive film
[0159] FIG. 3 is a flowchart illustrating a method for manufacturing a silicone adhesive film comprising a polysiloxane containing a methylphenyl group according to an embodiment of the present invention.
[0160] Referring to FIG. 3, a method for manufacturing a silicone adhesive film (S200) comprises the steps of: kneading a polysiloxane adhesive having at least one vinyl group and a polysiloxane containing a methylphenyl group to form a mixture (S210); adding a crosslinking agent and a platinum catalyst to the mixture and kneading to form a silicone adhesive composition (S220); applying the silicone adhesive composition onto a film substrate (S230); and curing the silicone adhesive composition (S240).
[0161] The step (S210) of forming the above mixture may be performed by mixing a polysiloxane adhesive having at least one vinyl group and a polysiloxane containing a methylphenyl group.
[0162] The above polysiloxane adhesive may have at least one vinyl group to enable peroxide crosslinking.
[0163] The above-mentioned polysiloxane containing a methylphenyl group comprises dimethyl siloxane (A); and methylphenyl siloxane (B) chemically bonded to the dimethyl siloxane, and the repeating unit may be AnB (wherein n is 15 or more and 300 or less).
[0164] The above mixture may include a solvent as described above. The solvent is based on the total weight of the mixture.
[0165] The step (S220) of forming the above silicone adhesive composition may be carried out by adding a crosslinking agent and a platinum catalyst to the mixture and kneading. At this time, a crosslinking reaction may occur.
[0166] The crosslinking agent and the platinum catalyst may be added to the mixture simultaneously or separately. For example, the crosslinking agent may be added to the mixture and mixed, and then the platinum catalyst may be added to the mixture and mixed. Alternatively, conversely, the platinum catalyst may be added to the mixture and mixed, and then the crosslinking agent may be added to the mixture and mixed.
[0167] In the above steps (S210, S220), the mixing can be performed in various ways, for example, using a mechanical stirrer.
[0168] The above mixing can be performed for various periods of time. In step (S210), the mixing can be performed, for example, for 30 minutes to 2 hours, and for example, for about 1 hour. In step (S220), the mixing can be performed, for example, for 10 minutes to 1 hour, and for example, for about 15 minutes after adding a crosslinking agent, and then for about 10 minutes after adding platinum.
[0169] The above application step (S230) can be performed by applying the silicone adhesive composition onto a film substrate.
[0170] The above coating may be performed by at least one of the following methods: drop coating, spin coating, drawdown coating, Mayer bar coating, doctor blade coating, slot die coating, dip coating, spray coating, inkjet coating, and roll coating.
[0171] The curing step (S240) above may be performed by curing the silicone adhesive composition. The curing step (S240) above, for example, 100 o C to 150 o It can be performed for 1 to 30 minutes at a temperature in the C range, for example, 130 o It can be performed for 10 minutes at a temperature of C.
[0172] In the above curing step (S240), the vinyl groups contained in the polysiloxane adhesive and the vinyl groups contained in the polysiloxane containing methylphenyl groups can be crosslinked by radical activity through the crosslinking agent. By such crosslinking, the silicone adhesive composition is cured, and a silicone adhesive film can be completed.
[0173] In the above curing step (S240), residual volatile substances are removed by heat, so that the physical properties of the silicone adhesive film can be stabilized, and the reaction termination of unreacted radicals can be induced by high-density chains.
[0174] Experimental example for silicone adhesive film
[0175] Preferred experimental examples are presented below to aid in understanding the present invention. However, the following experimental examples are intended only to aid in understanding the present invention and do not limit the present invention. Details not described herein can be sufficiently technically inferred by those skilled in the art, so their description is omitted.
[0176] Table 2 shows the component content of the silicone adhesive composition. For reference, Comparative Example 2 is a case that does not include methylphenyl polysiloxane but includes dimethylsiloxane.
[0177] Polysiloxane adhesive (g) Methylphenyl polysiloxane Crosslinking agent (g) platinum catalyst (g) division Content (g) Molecular weight (g / mol) Repetitive unit Methylphenyl fraction (%) Example 1 35 5 200000 AnB 2 0.5 1 Example 2 30 10 200000 AnB 2 0.5 1 Example 3 30 10 300000 AnB 2 0.5 1 Comparative Example 1 40 0 Not applicable Not applicable Not applicable 0.5 1 Comparative Example 2 30 10 180000 AAAA Not applicable 0.5 1 Comparative Example 3 30 10 200000 AABB 5 0.5 1 Comparative Example 4 30 10 300000 AABB 5 0.5 1 Comparative Example 5 20 20 200000 AnB 2 0.5 1
[0178] Referring to Table 2, the weight ratio of the polysiloxane adhesive and the polysiloxane containing a methylphenyl group (i.e., methylphenyl polysiloxane) is 7:1 for Example 1, 3:1 for Examples 2 and 3, and 1:1 for Comparative Example 5.
[0179] The manufacturing method is as follows. A polysiloxane adhesive and methylphenyl polysiloxane are mixed, and at room temperature (25 o C) was mixed with a mechanical stirrer for about 1 hour. Then, a crosslinking agent was added, and at room temperature (25 oC) was mixed with a mechanical stirrer for about 15 minutes. Then, a platinum catalyst was added, and at room temperature (25 o In C), the mixture was mixed with a mechanical stirrer for about 15 minutes. Accordingly, the silicone adhesive composition was formed.
[0180] Next, the silicone adhesive composition was applied to a fluorine release film by a drop coating method. The silicone adhesive composition was uniformly applied to the fluorine release film by a Mayer bar coating method.
[0181] The fluorine release film coated with the above silicone adhesive composition is 130 o A silicone adhesive film was formed by loading it into a heat treatment furnace of C and holding it for 10 minutes to cure it. At this time, a crosslinking reaction occurs.
[0182] The glass transition temperature of the above silicone adhesive film was measured using a TA DSC 250. The measurement method is as follows: 50 o -85 in C o After primary cooling to C, wait 10 minutes, and -85 o 50 in C o After heating to C for the first time, wait 10 minutes, and 50 o -85 in C o After secondary cooling to C, wait 10 minutes, and -85 o 50 in C o During the process of waiting 10 minutes after heating a second time to C, 5 o It was performed by scanning at a speed of C / min.
[0183] The peel strength of the above silicone adhesive film was measured. The measurement of the peel strength of the above silicone adhesive film was performed in accordance with ASTM D3330.
[0184] Table 3 is a table comparing the glass transition temperature and peel strength of a silicone adhesive film according to an embodiment of the present invention with that of a comparative example.
[0185] division Glass transition temperature ( o C) Peel strength (gf / in) Example 1 -27 1480 Example 2 -32 1430 Example 3 -39 1410 Comparative Example 1 27 1300 Comparative Example 2 32 760 Comparative Example 3 -15 770 Comparative Example 4 -8 810 Comparative Example 5 -52 1070
[0186] Referring to Table 3, the examples are -20 o It exhibited a glass transition temperature of C or lower and a peel strength of 1310 gf / in or higher. Therefore, the examples satisfy the scope of the present invention regarding glass transition temperature and peel strength.
[0187] At least one of the comparative examples does not satisfy the scope of the present invention with respect to glass transition temperature and peel strength.
[0188] Comparative Example 1 is a commercial product of HA-570A (SI Feliz Co., Ltd.) that does not contain methylphenyl polysiloxane. The glass transition temperature is 27 o C was very high, and the peel strength was relatively low at 1300 gf / in.
[0189] Comparative Example 2 is a case that does not include methylphenyl polysiloxane but includes dimethylsiloxane. Therefore, due to the linear polymer having AAAA repeating units, the glass transition temperature rises to 32 o C was very high, and the peel strength was very low at 760 gf / in.
[0190] Comparative Examples 3 and 4 have AABB repeating units, so the glass transition temperature is lowered due to the phenyl group (B) effect, but -15 o It was only at the C level, and as the tackiness decreased due to reduced compatibility with the resin caused by the phenyl group, the peel strength was very low at 770 gf / in.
[0191] Comparative Example 5 contains the same material as the present invention, but has a high content of methylphenyl polysiloxane. The glass transition temperature showed the lowest value. However, as the content of methylphenyl polysiloxane was excessive, the relative content of resin decreased, and consequently, the peel strength showed a low value. Since the peel strength decreased by more than about 20% compared to the original material Comparative Example 1, this is undesirable.
[0192] It will be obvious to those skilled in the art that the technical concept of the present invention described above is not limited to the aforementioned embodiments and attached drawings, and that various substitutions, modifications, and changes are possible within the scope of the technical concept of the present invention. Accordingly, the scope of rights of the present invention should be determined by the claims set forth below.
Claims
Claim 1 A polysiloxane adhesive having at least one vinyl group; and a polysiloxane containing a methylphenyl group that is cross-linked to the polysiloxane adhesive, wherein the polysiloxane containing the methylphenyl group comprises dimethylsiloxane (A); and methylphenylsiloxane (B) chemically bonded to the dimethylsiloxane, the repeating unit is composed of AnB (wherein is 15 or more and 300 or less), and the polysiloxane containing the methylphenyl group has the following chemical formula. (Here, n is 15 or more and 300 or less, and m is 2 or more and 256 or less) Silicone adhesive composition. Claim 2 In claim 1, the silicone adhesive composition is -20 o C to -50 o Silicone adhesive composition having a glass transition temperature in the C range. Claim 3 In claim 1, the silicone adhesive composition has a peel strength in the range of 1310 gf / in to 1500 gf / in. Claim 4 A silicone adhesive composition according to claim 1, wherein the polysiloxane adhesive and the polysiloxane containing a methylphenyl group are contained in a weight ratio of 2:1 to 10:
1. Claim 5 A silicone adhesive composition according to claim 1, wherein the polysiloxane containing a methylphenyl group has a molecular weight of 10,000 g / mol to 1,000,000 g / mol. Claim 6 delete Claim 7 In claim 1, the dimethylsiloxane is composed of a siloxane oligomer having the following chemical formula, Silicone adhesive composition. Claim 8 In claim 1, the methylphenylsiloxane has the following chemical formula, Silicone adhesive composition. Claim 9 In claim 1, the portion in which the dimethyl siloxane and the methylphenyl siloxane are bonded has the following chemical formula, in the polysiloxane containing the methylphenyl group. Silicone adhesive composition. Claim 10 In claim 1, the polysiloxane containing a methylphenyl group has at least one end portion comprising a vinyl group of the following chemical formula. Silicone adhesive composition. Claim 11 A silicone adhesive composition according to claim 1, wherein the methylphenylsiloxane is in the range of 0.1 mol% to 5 mol% with respect to the number n of repeating units of the dimethylsiloxane in the polysiloxane containing the methylphenyl group. Claim 12 A silicone adhesive composition according to claim 1, wherein the polysiloxane containing the methylphenyl group has a structure in which the An is respectively disposed at both ends. Claim 13 A silicone adhesive composition according to claim 1, wherein the polysiloxane adhesive comprises at least one of dimethyl polysiloxane, dimethyl diphenyl polysiloxane, dimethyl-methylphenyl polysiloxane, polydimethylsiloxane (PDMS), polymethylphenylsiloxane, dimethylsiloxane-methylphenylsiloxane copolymer, and dimethylsiloxane-diphenylsiloxane copolymer. Claim 14 A silicone adhesive composition according to claim 1, wherein the polysiloxane adhesive further comprises a resin composed of a network-type oligomer and having a vinyl group or a hydride group at the terminal end. Claim 15 The silicone adhesive composition according to claim 1 further comprises a crosslinking agent comprising at least one of dicumyl peroxide (DCP), 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane (DBPH), benzoyl peroxide (BPO), 2,4-dichlorobenzoyl peroxide (DBP), t-butyl peroxybenzoate (TBB), and α,α'-bis(t-butylperoxy)diisopropylbenzene (BIPB). Claim 16 A film substrate; and a silicone adhesive composition applied and cured on the film substrate, wherein the silicone adhesive composition comprises a polysiloxane adhesive having at least one vinyl group at a terminal end; and a polysiloxane containing a methylphenyl group cross-linked to the polysiloxane adhesive, wherein the polysiloxane containing a methylphenyl group comprises dimethylsiloxane (A); and methylphenylsiloxane (B) chemically bonded to the dimethylsiloxane, wherein the repeating unit is composed of AnB (wherein is 15 or more and 300 or less), and the polysiloxane containing a methylphenyl group has the following chemical formula. (wherein, n is 15 or more and 300 or less, and m is 2 or more and 256 or less) silicone adhesive film. Claim 17 In claim 16, the silicone adhesive composition is -20 o C to -50 o Silicone adhesive film having a glass transition temperature in the range of C and a peel strength in the range of 1310 gf / in to 1500 gf / in. Claim 18 The method comprises the steps of: kneading a polysiloxane adhesive having at least one vinyl group and a polysiloxane containing a methylphenyl group to form a mixture; adding a crosslinking agent and a platinum catalyst to the mixture and kneading to form a silicone adhesive composition; applying the silicone adhesive composition onto a film substrate; and curing the silicone adhesive composition, wherein the polysiloxane containing a methylphenyl group comprises dimethylsiloxane (A); and methylphenylsiloxane (B) chemically bonded to the dimethylsiloxane, and the repeating unit is composed of AnB (wherein is 15 or more and 300 or less), and the polysiloxane containing a methylphenyl group has the following chemical formula. (Here, n is 15 or more and 300 or less, and m is 2 or more and 256 or less) Method for manufacturing a silicone adhesive film. Claim 19 A method for manufacturing a silicone adhesive composition according to claim 18, wherein the polysiloxane containing a methylphenyl group is manufactured by a manufacturing method comprising the steps of: stirring a siloxane oligomer and a retardant to form a first mixture; stirring the first mixture and the methylphenyl siloxane to form a second mixture; stirring the second mixture and a platinum catalyst to form a third mixture; and heating the third mixture to polymerize the siloxane oligomer and the methylphenyl siloxane. Claim 20 A method for preparing a silicone adhesive composition according to claim 19, wherein, after performing the polymerization step, methylphenylsiloxane is added to the polymerized polysiloxane formed to form a polysiloxane having a desired molecular weight, and the polymerization reaction is repeated.
Citation Information
Patent Citations
Dual-curing adhesive composition and method for preparing and using the same
KR1020200043411A
Adhesive film with interpenetration polymer network, method for fabricating the same and foldable display device including the same
KR1020250046433A
Heat-curable siloxane encapsulant components
KR1020130068021A
Silicone pressure-sensitive adhesive composition
KR1020200035474A
Use of aryl-containing organopolysiloxane gums as additives to improve rheological behavior
KR1020220167327A
